Bimbingan Spiritual dan Sosial Guru Pendidikan Agama Islam terhadap Pembentukan Karakter Siswa di SMP YAPPA Depok - Hamzah Hamzah; Imam Tholkhah; Muhamad Faqihudin (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2020)
ABSTRACT Spiritual and Social Guidance of Islamic Education Teachers is one of the important factors in shaping the character of students. Which is in line with the National Education System Law of 2003. The current practice of Islamic Education tends to emphasize cognitive aspects, while the psychomotor aspects are rarely touched, including the planting of faith (apective aspects). This situation has triggered the imbalance of PAI learning outcomes, which in turn has created humans who are cognitively smart but spiritually and socially dry. Therefore the presence of Spiritual and Social Guidance activities is an alternative step to reduce or even cover the lack of developing apective and psychomotor aspects outside of school hours in the national curriculum. The purpose of this study was to find out how the spiritual and social guidance of Islamic Religious Education Teachers towards the Formation of Student Characters in Yappa Junior High School Depok. But specifically this research aims to find out: Programs, Supporting and Inhibiting Factors as well as the success of the spiritual and social guidance program of Islamic Religious Education Teachers Against the formation of student characters in Yappa Junior High School Depok. The research method used is descriptive analytic, which is to give an overview of what is happening. Data collected in the form of qualitative data obtained through interviews, observation, and study documentation. This research starts from a preliminary study of theories relating to the spiritual and social guidance of Islamic Religious Education Teachers, then looks for the location of schools that have spiritual and social guidance activities for their students. Data collection techniques, the author begins with observation, categorization, synthesis and compile working hypotheses, which of course are always accompanied by literature study. The conclusion obtained from this study is that the spiritual and social guidance of Islamic Religious Education Teachers Against the Formation of Student Character in Depok's Yappa Middle School is done well and effectively through religious activities, learning in class and examples which are routinely carried out in Depok's Yappa Middle School. Through this activity embodied the cultivation of spiritual and social values ​​in students of Depok Yappa Middle School, which is one of the efforts to achieve the objectives of Islamic Religious Education. The purpose of spiritual and social activities is in the context of establishing noble character among students, which includes material on faith, worship, morals, the Koran and history. The method used includes direct implementation (tajribi) riyadhoh, contemplation, advice. Keywords: spiritual and social guidance, islamic religious education teachers, student characteristics